2022
DOI: 10.3389/fendo.2022.907517
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Intermittently Scanned Continuous Glucose Monitoring in a Pediatric Population With Type 1 Diabetes: A Real World Study

Abstract: BackgroundUse of Continuous Glucose Monitoring (CGM) systems early in the course of diabetes has the potential to help glycemic management and to improve quality of life (QoL). No previous research has examined these outcomes in children-adolescents with type 1 diabetes (T1D) who use intermittently scanned CGM (isCGM) starting within the first month after diagnosis.AimTo evaluate the impact of isCGM early after T1D diagnosis, on metabolic control and QoL, comparing a group who started the use of the device wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…As the increase in daily scans pre-camp to camp was strongly associated with the improvement in TIR, the number of scans seem to have been a key to success in the isCGM group. This is an interesting finding, as the number scans in our study, are much higher than in other studies [9,[24][25][26][27]. A Suisse study in children with a T1D reported 6.5-9 scans per day [26], an Italian study reported a consistent number of 10 scans per day over the period of 1 year [25].…”
Section: Comparison Of Iscgm Vs Rtcgmsupporting
confidence: 49%
See 2 more Smart Citations
“…As the increase in daily scans pre-camp to camp was strongly associated with the improvement in TIR, the number of scans seem to have been a key to success in the isCGM group. This is an interesting finding, as the number scans in our study, are much higher than in other studies [9,[24][25][26][27]. A Suisse study in children with a T1D reported 6.5-9 scans per day [26], an Italian study reported a consistent number of 10 scans per day over the period of 1 year [25].…”
Section: Comparison Of Iscgm Vs Rtcgmsupporting
confidence: 49%
“…This is an interesting finding, as the number scans in our study, are much higher than in other studies [9,[24][25][26][27]. A Suisse study in children with a T1D reported 6.5-9 scans per day [26], an Italian study reported a consistent number of 10 scans per day over the period of 1 year [25]. The ALERTT1 study [9] in adults reported 11 scans per day.…”
Section: Comparison Of Iscgm Vs Rtcgmsupporting
confidence: 46%
See 1 more Smart Citation
“…Moreover, the analysis of glucose pattern may be used as an educational tool to demonstrate the relationship between an individual’s glucose levels, his/her medication, and other therapeutic interventions. There is evidence from observational studies that the early use (within one year from the diagnosis) of both isCGM [ 23 ] and rtCGM [ 24 26 ] results in long-term improvement in HbA 1c and the reduction in diabetes-related emergency-department admissions in people with type 1 diabetes. Moreover, the use of CGM at the onset of diabetes allows patients to be aware of the glycemic trends and their changes following insulin therapy.…”
Section: The Updated Algorithmmentioning
confidence: 99%
“…No. 225 patients with diabetes, aged 1–18 years were followed up in April 2022 [ 12 ], and participants (children–adolescents and their caregivers) were selected according to the following inclusion criteria:…”
Section: Methodsmentioning
confidence: 99%